Using information technology complete a practical introduction to computers & communications - Williams, Brian K. (McGraw Hill, 2013)
USING INFORMATION TECHNOLOGY; A Practical Introduction to Computers & Communications 10/e "If there is anything we have learned during 18 years of writing and revising this computer concepts book, it is this: Not only does the landscape of computer education change rapidly, but so do the students. . . . This edition, then, is written for the Always On generation, helping students use technology to enrich their personal lives." -Brian K. Williams & Stacey C. Sawyer